2020
DOI: 10.15829/1560-4071-2020-4032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intramyocardial haemorrhage on structural and functional echocardiographic parameters of myocardium after ST-segment elevation myocardial infarction with

Abstract: Aim. To analyze the effect of intramyocardial haemorrhage (IMH) on the structural and functional echocardiographic parameters of myocardium in patients with primary ST-segment elevation myocardial infarction (STEMI).Material and methods. The study included 60 patients with primary STEMI reperfused within 12 hours after symptom onset. On the second day after the event, all subjects underwent gadolinium-enhanced cardiac magnetic resonance imaging (MRI). IMH was visualized as T2-weighted hypointense areas. Subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
1
0
3
Order By: Relevance
“…The combination of MVO and IMH is a predictor of decreased LVEF in patients with primary STEMI. In addition, the correlation analysis results revealed a relationship between the area of IMH based on MRI, and LV systolic dysfunction based on echocardiography [ 28 ]. When studying the relation between MRI findings and adverse outcomes (CHF and SCD), it was found that infarct size, MVO, IMH, and low LVEF are related to major adverse cardiac events and provide the prognostic value [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of MVO and IMH is a predictor of decreased LVEF in patients with primary STEMI. In addition, the correlation analysis results revealed a relationship between the area of IMH based on MRI, and LV systolic dysfunction based on echocardiography [ 28 ]. When studying the relation between MRI findings and adverse outcomes (CHF and SCD), it was found that infarct size, MVO, IMH, and low LVEF are related to major adverse cardiac events and provide the prognostic value [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Комбинация МСО и ИМК является предиктором снижения ФВ ЛЖ у больных первичным ИМпST. Кроме того, по результатам корреляционного анализа выявлена взаимосвязь между площадью ИМК по МРТ и систолической дисфункцией ЛЖ по ЭхоКГ [13].…”
Section: Discussionunclassified
“…В отечественной научной литературе имеются единичные опубликованные работы, исследующие гетерогенность микрососудистого повреждения миокарда при ИМ с помощью МРТ сердца с контрастным усилением [9,12]. В предыдущих публикациях нами были подробно описаны клинико-лабораторные характеристики пациентов в зависимости от фенотипа микрососудистого повреждения миокарда, а также детально оценены показатели сократительной функции ЛЖ в ранний постин-фарктный период при ГПМ [13]. Настоящая работа является продолжением изучения прогностической роли разных фенотипов микрососудистого повреждения миокарда у пациентов с ИМпST.…”
Section: Discussionunclassified
“…В нашем исследовании данный фенотип микрососудистого повреждения миокарда регистрировался в 15 % случаев. В предыдущей работе нами впервые было описано, что изолированное ГПМ не оказывает значимого влияния на структурно-функциональные изменения миокарда ЛЖ в ранний постинфарктный период [13]. В настоящей работе впервые проведена оценка сократительной функции и размеров ЛЖ через 3 мес после индексного коронарного осложнения у пациентов с изолированным ГПМ.…”
Section: Discussionunclassified